Political Polarization: Challenges, Opportunities, and Hope for Consumer Welfare, Marketers, and Public Policy - Weber, T.J.; Hydock, Chris; Ding, William; Gardner, Meryl; Jacob, Pradeep; Mandel, Naomi; Sprott, David E.; Van Steenburg, Eric (Journal of Public Policy & Marketing, 2021)
Political polarization is a marked political division in the population, characterized by multiple manifestations. The authors argue that it can affect consumer psychology, which in turn influences marketers, policy makers, and consumer welfare. The present work introduces the construct of political polarization to the marketing literature and shows how it serves as a novel challenge for various marketing stakeholders. For consumers, the authors propose that political polarization increases the salience of political identities, alters inter- and intragroup dynamics, and amplifies cognitive biases. These effects negatively affect consumer welfare, including financial welfare, relationships, mental and physical health, and societal interests. For marketers, polarization introduces a challenge to both be more sociopolitically engaged while also navigating competing political interests. Polarization also creates new opportunities and challenges for segmentation, targeting, loyalty, and product offerings. For policy makers, political polarization creates policy gaps, impedes the implementation of policy, and obstructs governance. Building from these insights, the authors consider the drawbacks and overlooked benefits of political polarization, potential remedies, and directions for future research.
Keywords: dept.mrk; peer-reviewed

Metaphor elicitation: A new way to assess organizational culture - Prince, M.; Forr, J. (Psychologist-Manager Journal, 2021)
The purpose of this paper is to advance breakthrough research that further extends, as well as enrichens, our understanding of organizations. This is a companion article to “CEO Archetype Identity Drives Organization Culture” previously published in this journal. Archetypes are merely a special case of metaphors. In this paper, we generalize the concept of leadership archetypes to organization metaphors, adding original dimensions to existing concepts and theories of organizational diagnosis. Thus, the present research brings a new enlightening perspective to this field. Data from the past organization studies featured in this article involve the Zaltman Metaphorical Elicitation Technique (ZMET) embedded in qualitative in-depth personal interviews. These studies explore the impact of management styles on organization structure and functions. In each study metaphors were elicited from leaders and followers, and generated insights and action-oriented strategies to meet organizational challenges © 2021. American Psychological Association
Keywords: dept.mkt; peer-reviewed

Impact of risk aversion, reactance proneness and risk appraisal on travel destination risk perception: - Prince, Melvin; Kim, Young Kyu (Journal of Vacation Marketing, 2021)
The aim of the study is to investigate the motivational effects of tourist traits and risk appraisal on tourist destination risk perception. Risk appraisal involves subjective estimates of vulnerability to a threat and the threat’s consequential severity. Fear levels influence both of these elements of risk appraisal. Individual differences in reactance proneness and risk aversion are introduced into the study model to more fully account for differences in travel destination risk perceptions. The study design involves US adults, who have used their passports for international travel in the past 5 years. Travel risk assessments were studied for four destination sites: London, Tokyo, Kuala Lumpur and Istanbul. A general structural model is developed to test hypotheses about antecedents and consequents of risk appraisal and destination risk perception. © The Author(s) 2021.
Keywords: dept.mkt; peer-reviewed

Consumer responses toward symmetric versus asymmetric facial expression emojis - Hewage, G.S. Urumutta; Liu, Yue; Wang, Ze; Mao, Huifang (Marketing Letters, 2021)
Facial expression emojis are commonly used in digital communications and marketing campaigns. However, it is less known how the design of emojis may affect consumer responses. To address this gap, this research examines the impact of emojis’ facial asymmetry levels on consumer judgments. Findings across four studies demonstrate that compared with their symmetric counterparts, asymmetric facial expression emojis are more likely to receive favorable consumer evaluations. This effect is driven by perceptions of human expression resemblance and emotional expression strength and tends to be more prominent among consumers with a higher level of emotional sensitivity. Moreover, marketing messages including an asymmetric (vs. a symmetric) emoji are more likely to generate positive consumer responses.
Keywords: dept.mkt; peer-reviewed